2020
DOI: 10.3390/ijerph17165651
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Accelerometer-Based Intensity Prescription Compared to Physiological Variables in Pregnant and Nonpregnant Women

Abstract: Estimation of the intensity of physical activity (PA) based on absolute accelerometer cut points (Cp) likely over- or underestimates intensity for a specific individual. The purpose of this study was to investigate the relationship between absolute moderate intensity Cp and the first ventilatory threshold (VT1). A group of 24 pregnant and 15 nonpregnant women who performed a submaximal incremental walking test with measures of ventilatory parameters and accelerations from three different accelerometers on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Consistent with past studies [ 12 , 28 ], self-reported activity was typically higher than accelerometer data. One potential explanation for the discrepancy in self-report data, aside from recall bias, may be that the perceived exertion when engaging in physical activity increases as pregnancy progresses, and what is considered inactive pre-pregnancy may be considered active during pregnancy [ 29 , 30 ]. It also may be due to the cutoff points for moderate and vigorous activity being based on non-pregnant samples, and different cutoffs may be needed to adequately assess activity during pregnancy given the changes they are experiencing across gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with past studies [ 12 , 28 ], self-reported activity was typically higher than accelerometer data. One potential explanation for the discrepancy in self-report data, aside from recall bias, may be that the perceived exertion when engaging in physical activity increases as pregnancy progresses, and what is considered inactive pre-pregnancy may be considered active during pregnancy [ 29 , 30 ]. It also may be due to the cutoff points for moderate and vigorous activity being based on non-pregnant samples, and different cutoffs may be needed to adequately assess activity during pregnancy given the changes they are experiencing across gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding aim 1, 99 tests (including 75 different protocols) were used to assess CRF,8 12 13 18 27–108 28 (including 16 different protocols) to assess muscular fitness,8 12 13 61 86 109–122 14 (including 13 different protocols) to assess flexibility,12 13 110 114 123–127 45 tests (including 40 different protocols) to assess balance,110 116 128–167 2 tests using the same protocol to assess speed168 169 and 3 tests using the same protocol were multidimensional 168–170. No results were found for other PF components such as agility or coordination.…”
Section: Resultsmentioning
confidence: 99%
“…Studies comparing 24-HMBs in isolation were also considered but we did not find studies whose results were directly comparable with this study. The comparability of studies reporting on the convergence between ActiGraph and Axivity to measure PA and/or SB was hampered by: (1) the variability in the location where one or both devices were worn (e.g., hip versus wrist) [ 15 ], (2) behavioral conceptualization (e.g., steps versus intensity) [ 16 ], (3) the setting (e.g., field-based versus laboratory) [ 17 ], and (4) the use of different data processing methods (e.g., GGIR versus OMGui) [ 18 ]. Although we found no studies of which the results were generalizable to this study, our results are consistent with the major finding of Rosenberger and colleagues’ (2016) review that several wearable devices are not able to accurately measure MVPA (with the ActiGraph used as criterion measure).…”
Section: Discussionmentioning
confidence: 99%